Epidemiological Factors Associated With Caligus rogercresseyi Infection, Abundance, and Spatial Distribution in Southern Chile - Lepe-López, Manuel; Escobar-Dodero, Joaquín; Rubio, Daniel; Alvarez, Julio; Zimin-Veselkoff, Natalia; Mardones, Fernando O. (Frontiers in Veterinary Science, 2021)
Sea lice (Caligus rogercresseyi) is an external parasite that affects farmed salmonid in Chile, with dramatic sanitary and economic impacts. Despite space-time patterns suppose aggregation, specific locations related to different infestation levels, and factors associated crossways the geographic range had not been investigated yet. The understanding effects factors can be considered for integrated pest management (IPM). In the present study, the multivariate spatial scan statistic was used to identify geographic areas and times of C. rogercresseyi infestation and estimate the factors associated with such patterns. We used official C. rogercresseyi monitoring data at the farm level with a set of 13 covariates to provide adjustment within the analyzes. The analyses were carried out across five years (2012-2016) and between three fish species (Salmo salar, Oncorhynchus mykiss, and, O. kisutch) to assess the consistency of the identified clusters. A retrospective multinomial, spatial, and temporal scan test was implemented to identify farms clusters of either different categories of C. rogercresseyi infected farms: baseline, medium, and high based on the control chemical threshold of the health authority. The baseline represents an adequate performance against C. rogercresseyi infection. Then, the production and environmental factors of the medium and high infection were compared with the baseline using regression techniques. The results revealed 26 clusters (p < 0.001) of which 12 correspond to the baseline, whereas one is a medium, and 13 are high infection clusters were detected. In general, the clusters of the baseline are detected in a latitudinal gradient on estuarine areas, with increasing relative risks to islands system waters complex. There is a spatial structure in specific sites (northern of Los Lagos region and central Aysén region) with high infection clusters and epidemic peaks during 2013. In addition, average weight, salmon species, chemical control ingredient, latitude, temperature, salinity, and year category are factors associated with these patterns. Recommendations for IPM plan are provided along with a discussion considering to involve stock density thresholds by salmon species and the spatial structure of the efficacy of chemical control to avoid the advance of resistance and to minimize environmental residues.